The The Influence Of Brand Image, Brand Awareness, Brand Trust, And Halal Label On Purchasing Decisions At Rocket Chicken Products. - Tri Septin Muji Rahayu Rahayu; Basma Nur Cholifah Cholifah; Nawalin Nazah Nazah; Erny Rachmawati Rachmawati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to examine the influence of brand image, brand awareness, brand trust, and halal labeling on purchasing decisions at Rocket Chicken outlets in Purwokerto. Indonesia’s fast-food industry continues to grow rapidly, increasing competition among halal fried chicken brands. This quantitative research involved 110 respondents selected through purposive sampling. Data were analyzed using SPSS 26 with descriptive analysis and multiple linear regression. The results show that brand image (β = 0.369; t = 5.380; Sig = 0.000), brand trust (β = 0.234; t = 2.085; Sig = 0.040), and halal labeling (β = 0.239; t = 2.380; Sig = 0.019) significantly and positively affect purchasing decisions. Meanwhile, brand awareness (β = 0.153; t = 1.445; Sig = 0.151) does not have a significant effect. The regression model obtained is Y = –1.460 + 0.369X₁ + 0.153X₂ + 0.234X₃ + 0.239X₄ + e. In conclusion, the study provides quantitative evidence that purchasing decisions at Rocket Chicken are primarily driven by brand image, consumer trust, and halal certification, while awareness alone is insufficient. These findings offer strategic implications for improving marketing effectiveness in the fast-food sector.